Mengukur Transparansi Pelaporan Segmen Usaha pada Industri Barang Konsumsi: Kepatuhan terhadap PSAK 5 - Aisha Candra Dewi; Rimi Gusliana Mais (Indonesian Journal of Applied Accounting and Finance, 2025)
Companies that are diversified in Indonesia and have been registered on the IDX or have gone public are required to prepare consolidated financial reports and report the company's segment finances. Segment financial reports are an important part of a company's financial reports, especially for entities that have various business lines or operate in various geographic areas. This research aims to analyze segments according to the ten percent test of income, profit and loss and assets in the 2022-2023 PT Unilever Tbk Annual Report. This research uses qualitative methods with secondary data and data analysis techniques. The results of this research show that all segments at PT Unilever Tbk comply with the provisions of PSAK 5. Even though each segment experiences a decrease or increase per year. PT Unilever's compliance with PSAK 5 strengthens the transparency of segment financial reports for investors and regulators, although performance fluctuations between segments require management vigilance. Academically, this finding forms the foundation for further studies on the dynamics of segment reporting in diversified companies, especially regarding the impact of business volatility on accounting standards compliance.